2000
DOI: 10.4049/jimmunol.165.4.1733
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Naive T Cells Masquerading as Memory Cells

Abstract: This study shows that naive CD8 T cells can acquire characteristics of memory T cells in the absence of stimulation with specific Ag simply by the process of homeostatic proliferation under lymphopenic conditions. This Ag-independent T cell differentiation pathway did not result in up-regulation of early activation markers (CD69, CD25, CD71), but expression of several memory markers (CD44, CD122, Ly6C) increased progressively with successive divisions. These markers were then stably expressed, and these cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
399
4
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 428 publications
(451 citation statements)
references
References 25 publications
40
399
4
6
Order By: Relevance
“…The model predicts that the turnover rates are division number dependent. Similar analysis of in vivo data on the dynamics of P-14 tg CTL after adoptive transfer into irradiated mice [13] confirmed our findings. Therefore, the use of homogenous models for the analysis of cell kinetics deserves a caution.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The model predicts that the turnover rates are division number dependent. Similar analysis of in vivo data on the dynamics of P-14 tg CTL after adoptive transfer into irradiated mice [13] confirmed our findings. Therefore, the use of homogenous models for the analysis of cell kinetics deserves a caution.…”
Section: Resultssupporting
confidence: 89%
“…In [9], the model variables A j (t) + B j (t) were fitted to in vivo data on proliferation of P-14 Tg naive CD8 T cells after adoptive transfer into an irradiated host, taken from [13] and summarized in Table 3 in [9]. A partly heterogenous version of the above model, in which the division and death rates of naive cells are different from those of the divided cells, was studied in [6] on in vitro data from [10].…”
Section: A Version Of Smith-martin Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been observed that transfer of small numbers of T cells into lymphopenic hosts results in T-cell expansion, a process described as homeostatic proliferation [9][10][11][12][13][14][15][16]. As the T cells proliferate, they assume an Ag-experienced or memory phenotype, which is indicated by upregulation of CD44, Ly6C and CD122 (IL-2-IL-15Rβ) [12,15].…”
Section: A Link Between Lymphodepletion and Augmented Immune Functionmentioning
confidence: 99%
“…As the T cells proliferate, they assume an Ag-experienced or memory phenotype, which is indicated by upregulation of CD44, Ly6C and CD122 (IL-2-IL-15Rβ) [12,15]. This T-cell expansion and acquisition of a memory phenotype is also associated with enhanced effector functions, determined by ex vivo analysis of interferon-γ (IFN-γ) release and cytolysis [12,14,15].…”
Section: A Link Between Lymphodepletion and Augmented Immune Functionmentioning
confidence: 99%